Nurses' Knowledge about Cardio-Pulmonary Resuscitation in Mosul City - Mahmoud Mohammed Ahmed; Nasir Mufaq Youns; Ahmed Ali Hussein (College of Nursing,University of Mosul, 2017)
Background and Objectives: Resuscitation in hospitals and health care facilities, refers to prompt actions aimed to prevent death and providing the best possible chances for human survival. The study aims to assess the nurses' knowledge towards cardiopulmonary resuscitation and to identify the relationship between nurses' knowledge about cardiopulmonary resuscitation and some demographic variables (age, gender, educational level, work place and years of experience). Material and method: A descriptive study design was adapted to assess the knowledge of the nurses regarding CPR. The sample of the study consist of (122) nurses, (26) female, and (96) male who works in Iben-Sena and Al-Zahrawe teaching hospitals in Mosul City. The sample of the study was selected in the simple random method. Data were collected by using a questionnaire throughout an interview technique. The questionnaire consists of two parts, Part one consists of (5 items) includes some demographic data including age, gender, educational level, work place and previous experience. Part two consists of (23 items) include questions that assess the nurses' knowledge towards cardiopulmonary resuscitation. Data were analyzed and calculated by using SPSS program. Results: The nurses' knowledge score regarding cardiopulmonary resuscitation record low, (27.942%), and standard deviation (0.609). Conclusion: The present study reveals that the nurses have poor knowledge regarding the CPR techniques and there are no significant difference between nurses' knowledge about cardio pulmonary resuscitation with demographic characteristics except work place and gender. Keywords: Knowledge, Cardiopulmonary resuscitation.